Public Utility. The process structured by the São Paulo Architecture Biennial: a platform of investigation and the articulation of a conste- llation of actions in the territory - L. Rosa, Marcos (2019)
In this paper we present the construction process of the 11th edition of the São Paulo Architecture Biennial, carried out between 2016 and 2018, focusing on its structure as a research platform.Throughout the text we present a brief narrative about the process of construction of the Biennial, the definition of its format – which emphasizes the action in the territory – culminating in a critical review of the event in the current conjuncture of the field of architecture considering its social and political approach. With a focus placed in the geography of its own territory, the city of São Paulo, we present a constellation of actions, that is, a series of ‘places’ articulated by the event. Based on that experience we promoted a localized and situational reflexion, also globally articulated, introducing the challenges of its process and the outcomes of the event, including the register of the legacy proposed by that format.